THU0212 BARICITINIB-ASSOCIATED CHANGES IN GLOBAL GENE EXPRESSION DURING A 24-WEEK PHASE 2 CLINICAL SLE TRIAL DESCRIBE A MECHANISM OF ACTION THROUGH INHIBITION OF JAK/STAT AND IFN RESPONSIVE GENE EXPRESSION. (June 2019) - Dörner, Thomas; Tanaka, Yoshiya; Petri, Michelle A; Smolen, Josef S.; Dow, Ernst; Higgs, Richard E; Rocha, Guilherme; Benschop, Robert; Silk, Maria; Bono, Stephanie de; Hoffman, Robert
Abstract : Background: Baricitinib (bari) is an oral selective Janus kinase (JAK)1 and JAK2 inhibitor. In the Phase 2 study, JAHH (NCT02708095 ), treatment with bari resulted in significant improvements in patients (pts) with active systemic lupus erythematosus (SLE) receiving standard background therapy, compared with placebo (PBO). 1 Objectives: To use global gene expression to characterize baseline (BL) gene expression among SLE pts in JAHH and to describe the mechanism of action (MoA) of bari during treatment in active SLE. Methods: A total of 314 pts were randomized 1:1:1 to PBO, bari 2-mg, or bari 4-mg once daily for 24 weeks (Wks) in JAHH. RNA isolated from whole blood at BL and Wks 2, 4, 12, and 24 was analyzed using HTA2.0 arrays, possessing over 925, 000 specific individual probes. Data were summarized to transcript level and analyzed using a mixed effects model on a log2 transformed response with multiplicity correction. Results: Baseline gene expression analysis comparing healthy controls to SLE pts revealed elevated expression of genes involved in innate and adaptive immune pathways and biologic processes thought to be key to SLE pathogenesis. Baseline findings from the ILLUMINATE trial of tabalumab (1760 SLE pts at BL) 2 were independently replicated, including individual gene-specific changes in the SLE populations versus controls. Treatment-induced changes were predominantly observed in the bari 4-mg versus PBO group at early time points (Wks 2 and 4; bari 4-mg > 2-mg). Statistically significant changes were observed for type I and II IFN responsive genes, and in the JAK/signal transducer and activator of transcription (STAT) canonical and noncanonical signaling pathways, in the bari 4-mg versus PBO group comparisons. There were biologically notable and statistically significant bari-associated decreases in gene expression from BL, compared to PBO, for interleukin (IL)-3, -5, -6, -7, and granulocyte macrophage colony-stimulating factor pathways, attributable to inhibition of JAK/STAT signaling. Conclusion: These results build upon previous studies of gene expression in ILLUMINATE, comparing SLE at BL with healthy controls; they advance our understanding of lupus pathogenesis, and further delineate the MoA of bari in SLE. These data independently confirm the marked elevations of specific type I and II IFN genes at BL in clinical trial pts on standard of care treatment. Changes in gene expression with bari impacted IFN responsive genes as well as JAK/STAT signaling pathways. Interpretation of results is limited by sample size and statistical power, and presence of concomitant medications. Importantly, gene expression may not translate directly to protein expression; however, ongoing proteomic studies (including specific assays for type I IFN, IFN-γ, IL-12, IL-17, and IL-23) will help extend these gene expression results and further describe the MoA of bari in SLE. References: [1] Wallace D, et al. Lancet. 2018;392:222-231 [2] Hoffman R, et al. Arthritis Rheumatol. 2017;69:643-654 Disclosure of Interests: Thomas Dörner Grant/research support from: Eli Lilly, Janssen, Roche, UCB Pharma, Consultant for: Eli Lilly, Janssen, Roche, UCB Pharma, Speakers bureau: Eli Lilly, Janssen, Yoshiya Tanaka Grant/research support from: Abbvie, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eisai, Mitsubishi-Tanabe, MSD, Ono, Taisho-Toyama, Takeda, Speakers bureau: Abbvie, Asahi-kasei, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eli Lilly, Eisai, Glaxo-Smithkline, Janssen, Mitsubishi-Tanabe, Novartis, Pfizer Japan Inc, Sanofi, Takeda, UCB, YL Biologics, Michelle A Petri Shareholder of: Pfizer, Merck, Grant/research support from: AstraZeneca, Exagen, Consultant for: Eli Lilly, GSK, Merck EMD Serono, Janssen, Amgen, Novartis, Quintiles, Exagen, Inova Diagnostics, AstraZeneca, Blackrock, Glenmark, UCB, and the Annenberg Center for Health Sciences, Josef S. Smolen Grant/research support from: AbbVie, Eli Lilly, Janssen, MSD, Pfizer Inc, Roche, Consultant for: AbbVie, Amgen, AstraZeneca, Astro, Celgene, Celtrion, Eli Lilly, GlaxoSmithKline, ILTOO, Janssen, Medimmune, MSD, Novartis-Sandoz, Pfizer Inc, Roche, Samsung, Sanofi, UCB, Speakers bureau: AbbVie, Amgen, AstraZeneca, Astro, Celgene, Celtrion, Eli Lilly, GlaxoSmithKline, ILTOO, Janssen, Medimmune, MSD, Novartis-Sandoz, Pfizer Inc, Roche, Samsung, Sanofi, UCB, Ernst Dow Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Richard E Higgs Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Guilherme Rocha Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Robert Benschop Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Maria Silk Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Stephanie de Bono Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Robert Hoffman Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company